Tissue distribution and excretion of the five components of Portulaca oleracea L. extract in rat assessed by UHPLC - Wenjie Zhang; Di Li; Aijing Leng; Junjun Ai; Yang Du; Yihan Meng; Yucong Gao; Xixiang Ying (Universidade de São Paulo, 2015)
The aim of the present study was to investigate the tissue distribution and excretion of five components of Portulaca oleracea L. extract (POE) in rat following oral administration. A rapid, sensitive and specific ultra-high performance liquid chromatography (UHPLC) method with puerarin as the internal standard was used for the quantitative analysis of five components of POE, including caffeic acid (CA), p-coumaric acid (p-CA), ferulic acid (FA), quercitrin (QUER) and hesperidin (HP) in rat tissues including the liver, intestine, stomach, muscle, heart, lung, brain, kidney and spleen, urine and feces. The results show that onlyp-CA and FA were found in nearly all tissues with low cumulative ratios, and CA was higher in the intestine and stomach with a slightly higher cumulative ratio in the urine and feces after 24 h. HP and QUER were found at low levels in the tissues with low cumulative ratios.